Roles of Chitosan in Green Synthesis of Metal Nanoparticles for Biomedical Applications - Phan, Thi Tuong Vy (Nanomaterials (Basel), 2021)
Chitosan (CS) is a well-known stabilizer for metal nanoparticles in biomedical engineering. However, very few studies have explored other important roles of CS including reducing, shape-directing, and size-controlling. This review aims to provide the latest and most comprehensive overview of the roles of CS in the green synthesis of metal nanoparticles for biomedical applications. To the best of our knowledge, this is the first review that highlights these potentialities of CS. At first, a brief overview of the properties and the bioactivity of CS is presented. Next, the benefits of CS for enhancing the physicochemical behaviors of metal nanoparticles are discussed in detail. The representative biomedical applications of CS-metal nanoparticles are also given. Lastly, the review outlines the perceptual vision for the future development of CS-metal nanoparticles in the biomedicine field.